2008
DOI: 10.1143/ptps.172.224
|View full text |Cite
|
Sign up to set email alerts
|

On the Riemann Curvature Tensor in General Relativity

Abstract: The general theory of relativity is a theory of gravitation in which gravitation emerges as the property of the space-time structure through the metric tensor g ij . The metric tensor determines another object (of tensorial nature) known as Riemann curvature tensor. At any given event this tensorial object provides all information about the gravitational field in the neighbourhood of the event. It may, in real sense, be interpreted as describing the curvature of the space-time. The Riemann curvature tensor is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
8

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 2 publications
0
2
0
8
Order By: Relevance
“…In Ahsan and Siddiqui [6] showed that a perfect fluid spacetime has divergencefree projective curvature tensor if and only if the Ricci tensor S is of Codazzi type. Also, Ahsan and Ali [3] proved that for a perfect fluid spacetime M with divergencefree projective curvature tensor, if the Ricci tensor S is covariantly constant, then M is of constant curvature and, respectively, if the energy-momentum tensor T is of Codazzi type, then r À 3p is constant.…”
mentioning
confidence: 99%
“…In Ahsan and Siddiqui [6] showed that a perfect fluid spacetime has divergencefree projective curvature tensor if and only if the Ricci tensor S is of Codazzi type. Also, Ahsan and Ali [3] proved that for a perfect fluid spacetime M with divergencefree projective curvature tensor, if the Ricci tensor S is covariantly constant, then M is of constant curvature and, respectively, if the energy-momentum tensor T is of Codazzi type, then r À 3p is constant.…”
mentioning
confidence: 99%
“…El tensor de curvatura (Tensor de Riemann), R , es un tensor del tipo (1,3), cuyas componentes son R a bcd , se puede descomponer de forma única en partes que son representaciones irreducibles del grupo completo de Lorentz…”
Section: Invariantes De Curvatura Polinomialesunclassified
“…# esto ayuda a no visualizar la dependencia en las variables utilizadas Variedad > g := evalDG(−A(t) dX [1] &t dX [1] + B(t) dX [2] &t dX [2] + r 2 (dX [3] &t dX [3] + sin 2 (θ) dX [4] &t dX [4])) # Con este comando dotamos una métrica a nuestra variedad creada y &t denota el producto tensorial. Variedad > A sol := (simpli f y@value@eval@subs)(B sol , sol [2][]) # sustituimos la solución B dentro de la solución A con (eval@subs);…”
Section: Solución De Schwarzschild Con Mapleunclassified
See 2 more Smart Citations